Empowering Female-Headed Households: Assessing the Impact of a Leadership Mentoring Program in Rural Indonesia - Novianty Djafri; Syamsu Qamar Badu; Heldy Vanni Alam; Isnanto Isnanto; Nina Lamatenggo (PPSDP International Journal of Education, 2026)
The leadership management mentoring program for female-headed households, implemented through the Women Empowerment School in Hutamonu Village (Tanah Wangi), Boliyohuto Subdistrict, Boalemo Regency, was designed to enhance women’s leadership capacity in managing both family and community affairs. Female-headed households often face multiple challenges, including limited decision-making power, financial constraints, and restricted participation in community development. Strengthening their leadership and management capacity is therefore essential to improving family welfare and fostering inclusive rural development. The objectives of the program were: (a) to strengthen the leadership capacity of female-headed households in managing families and communities; (b) to increase women’s awareness and abilities in decision-making and financial management; and (c) to improve the overall quality of life for women and their families in Hutamonu Village. The program was implemented through leadership training and mentoring activities, employing a survey research design with a qualitative approach, and the findings were presented in a descriptive narrative form. Data were collected through questionnaires, in-depth interviews, observations, and documentation, ensuring a comprehensive understanding of both individual and collective changes. The results indicate that the program significantly improved the leadership skills of female-headed households, enhanced their awareness and decision-making capacity, and strengthened their financial management abilities. Furthermore, the program contributed to raising the quality of life for women and their families, while also increasing their participation in community development initiatives. In conclusion, the mentoring program demonstrates that targeted leadership and empowerment interventions can foster sustainable improvements in women’s capacities and promote equitable rural development.